Knowledge on retirement related financial planning among employees - Mohd Noar, Nor Zaihan (IIUM Press, International Islamic University Malaysia, 2018)
This study was carried out to assess the knowledge on retirement financial planning among IIUM employees. Among factors that were taken into consideration in assessing this are exposure provided by employers either formal or informal on financial planning, personal opinion on best time to start on financial planning for retirement, setting financial goal and type of investment for retirement and assessing respondent opinion on the adequate amount of savings for retirement life. In creating a more meaningful analysis to this study, demographic factors are used to link to the knowledge on retirement related planning. The methodology used in this study was quantitative, involving distribution of questionnaire to respondents to collect primary data. With respect to the knowledge on retirement planning, it was found that 58% of the respondents said that they do not get any formal exposure on financial retirement planning while the remaining claimed getting it on an informal basis. In setting financial goal for financial retirement planning, more than 50% of the respondents felt that the best time to start financial planning for retirement is from between the age of 25-35 years old. Majority of the respondents claimed to have a financial goal when they retire and in achieving it they prefer to invest in unit trusts. The findings also prove that demographic factors such as age, educationand income level play an important role in financial retirement planning. It is also recommended that employers and the government should take more initiatives in providing training to enhance the knowledge and awareness of financial retirement planning among employees.